Design of the Vitesse Intracranial Stent Study for Ischemic Therapy (VISSIT) Trial in Symptomatic Intracranial Stenosis - Zaidat, Osama O.; Castonguay, Alicia C.; Fitzsimmons, Brian-Fred; Woodward, Britton Keith; Wang, Zhigang; Killer-Oberpfalzer, Monika; Wakhloo, Ajay; Gupta, Rishi; Kirshner, Howard; Eliasziw, Misha; Thomas Megerian, J.; Shetty, Sujith; et al. (Journal of stroke and cerebrovascular diseases, 2013)
Patients with high-grade symptomatic intracranial stenosis (≥70%) have an increased risk of recurrent stroke despite medical treatment with antiplatelet or anticoagulant therapy. Intracranial stenting has been proposed as a viable treatment option for this high-risk patient population; however, evaluation of this therapy in randomized multicenter trials is needed. In this article, we present the design and methods of the Vitesse Intracranial Stent Study for Ischemic Therapy (VISSIT) trial for symptomatic intracranial stenosis. The VISSIT trial is a randomized control study designed to evaluate the safety, probable benefit, and effectiveness of the PHAROS Vitesse neurovascular balloon-expandable stent system plus medical therapy versus medical therapy alone in patients with cerebral or retinal ischemia due to neurovascular stenosis (≥70%) for preventing the primary composite end point: stroke in the same territory (distal to the target lesion) as the presenting event within 12 months of randomization or hard transient ischemic attack in the same territory (distal to the target lesion) as the presenting event from day 2 through month 12 postrandomization. Enrollment began in February 2009 and was halted in January 2012 with 112 subjects enrolled into the study. Clinical follow-up will continue for the planned period of 12 months postrandomization. The VISSIT trial may provide valuable insight into the use of balloon-expandable intracranial stent as a treatment option for high-risk patients. Lessons learned from this trial may better guide future clinical trial design on best patient selection, stenting techniques, and periprocedural management.